Current Synodal Process: An Effort to Promote an Ecclesial Culture of Serious Listening to the Sensus Fidei - Tirimanna, Vimal (Asian Horizons, 2024)
According to the cherished Christian belief, when a person is baptized, the Holy Spirit not only anoints him/her, but begins to dwell in him/her. Because of this indwelling of the Spirit, the baptized as persons and as a whole are kept from falling into error with regard to matters to do with faith and morals, by the same Spirit. This supernatural instinct, known as sensus fidei is the characteristic of the fact that it is the Holy Spirit who guards and guides the Church as a community of believers. Although sensus fidei is affirmed and reaffirmed by Church authorities, especially after Vatican-II, in practice it has not been taken that seriously in ecclesial life, till the election of Pope Francis in 2013. His launching of the current synodal process in the worldwide Church has re-awakened this theological concept. Since the main aim of this process is to inculcate a culture of consulting and active listening in all spheres of Church life, it is hoped that eventually sensus fidei will be allotted its due place. This article is an effort not only to describe what this concept would imply (if taken seriously) in ecclesial life, but also to highlight a few obstacles one faces in putting it into practice in the contemporary ecclesial life.